EVALUASI PASCA HUNI BANGUNAN BRAGA CITY WALK BANDUNG - ASTRID AUSTRANTI YUWONO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Braga City Walk is located at Jalan Braga which is a conservation area in Bandung city. Braga region used to be the main attraction of Bandung which was known as â€œParijs van Javaâ€. Few years ago Braga was in derelict condition that is shown by the old buildings that are mostly less well maintained as well as the economic activities that are less passionate. Braga City Walk was designed as a themed lifestyle center, which further highlight the entertainment activities and recreational/leisure activities than just shopping. Braga City Walk conditions now still have a large amount of rental space that is empty, the changes that have been made during its development showthat they tried to change that situation. This research was conductedtomake apost-occupancy evaluation at indicativelevel. The method usedare literatures review, collectingdatafrom buildingâ€™s drawings, and with awalk-through observationof eachpath of the interior which will generatethe physical factorsincludethe location, the layout ofthe environment, spatial, circulatory system, as well asmaterial. Theobservation ofenvironmental backgroundwill producenon-physical factors includedevelopment ofcomplexenvironments, management ofthe complex, as well asuser behavior.In the case of Braga City Walk, factors affecting the value of this building is the determination of the function (physical factor), in this case the consideration of the character of rental space, which then affects the spatial design and immediately establish the circulation patterns within the building. Since the judgment rooted in the character of the room rent, the solution is to create a new concept bypay attention to the potential of the surrounding environment (non-physical factor). Furthermore, the physical improvement that absolutely must be done is to reshape the circulation pattern of the ideal circuit, where visitors directed convenient to go around the complex without encountering dead-end spaces.Â Keywords: bragacity walk; circulation; planning; post-occupancy evaluation; space